Electronic Health Records and Meaningful Use in Local Health Departments: Updates From the 2015 NACCHO Informatics Assessment Survey - Williams, Karmen S. (J Public Health Manag Pract, 2016)
Electronic health records (EHRs) are evolving the scope of operations, practices, and outcomes of population health in the United States. Local health departments (LHDs) need adequate health informatics capacities to handle the quantity and quality of population health data. PURPOSE: The purpose of this study was to gain an updated view using the most recent data to identify the primary storage of clinical data, status of data for meaningful use, and characteristics associated with the implementation of EHRs in LHDs. METHODS: Data were drawn from the 2015 Informatics Capacity and Needs Assessment Survey, which used a stratified random sampling design of LHD populations. Oversampling of larger LHDs was conducted and sampling weights were applied. Data were analyzed using descriptive statistics and logistic regression in SPSS. RESULTS: Forty-two percent of LHDs indicated the use of an EHR system compared with 58% that use a non-EHR system for the storage of primary health data. Seventy-one percent of LHDs had reviewed some or all of the current systems to determine whether they needed to be improved or replaced, whereas only 6% formally conducted a readiness assessment for health information exchange. Twenty-seven percent of the LHDs had conducted informatics training within the past 12 months. LHD characteristics statistically associated with having an EHR system were having state or centralized governance, not having created a strategic plan related to informatics within the past 2 years throughout LHDs, provided informatics training in the past 12 months, and various levels of control over decisions regarding hardware allocation or acquisition, software selection, software support, and information technology budget allocation. CONCLUSION: A focus on EHR implementation in public health is pertinent to examining the impact of public health programming and interventions for the positive change in population health.